"The Space of Words": Exile and Diaspora in the Works of Nelly Sachs. By Jennifer M. Hoyer. Rochester, NY: Camden House. 2014. - Lynda K Nyota (Studies in 20th & 21st Century Literature, 2017)
Review of "The Space of Words": Exile and Diaspora in the Works of Nelly Sachs. By Jennifer M. Hoyer. Rochester, NY: Camden House. 2014.
Keywords: Hoyer; Sachs; Jewish Authors; Trauma; Holocaust